ZIF-derived CoZnS electrode material and preparation method and application thereof
By introducing the ZIF-67 structure on the two-dimensional transition metal sulfide material and sulfide treatment, a ZIF-derived CoZnS electrode material with high specific surface area and catalytic site density was prepared, and the low catalytic site density in the prior art was solved. Problem, significantly improving the electrocatalytic hydrogen evolution performance.
Patent Information
- Application Number
- CN202411723877.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing two-dimensional transition metal sulfide materials have low catalytic site density during catalytic hydrogen evolution reaction, and the preparation method has limited effect on increasing edge positions of the two-dimensional layered structure, resulting in unsatisfactory electrocatalytic performance.
ZIF-derived CoZnS electrode material is used to prepare foam nickel-CoZn precursors through solvothermal reaction, and a ZIF-67 structure is introduced on it, followed by vulcanization to form a ZIF-derived CoZnS electrode material with a stable three-dimensional structure.
The specific surface area and catalytic site density of the electrode material are improved, the catalytic activity and electrocatalytic hydrogen evolution performance are enhanced, and the problem of low catalytic site density in the prior art is overcome.
Smart Images

Figure CN119491261A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrode materials, and particularly relates to a ZIF-derived CoZnS electrode material and a preparation method and application thereof. Background Art
[0002] As a highly promising sustainable clean energy, hydrogen energy has zero emissions and high energy density, making it an ideal choice to replace fossil fuels. However, traditional hydrogen production methods are often energy-intensive and costly, and some processes rely on fossil fuels, which limits the large-scale commercial application of hydrogen energy. Therefore, exploring efficient and environmentally friendly hydrogen production technologies, especially catalytic hydrogen evolution reactions driven by renewable energy, has become a hot topic in current research.
[0003] Currently, the production pathways of hydrogen include different methods such as fossil fuel reforming and water electrolysis. Among these methods, water electrolysis is considered to be a promising method for hydrogen production because it is environmentally friendly and the reactant water is abundant and renewable, so people are paying more and more attention to the research of electrode materials for water decomposition. In order to achieve efficient and economical hydrogen production by water electrolysis, the key is to develop electrocatalysts with high catalytic performance, high stability and low cost. At present, the catalysts used in electrochemical water splitting technology mainly include those based on precious metals, transition metals and metal-organic framework compounds. The challenge is that metal catalysts have poor stability in acidic environments, while precious metal-based catalysts have the disadvantages of high cost and scarce sources. In addition, precious metal-based catalysts require high overpotentials for hydrogen evolution reactions in alkaline media, which are not suitable for large-scale industrial applications.
[0004] At present, two-dimensional transition metal sulfide materials have attracted widespread attention in the field of catalysis due to their unique atomic configuration and electronic structure. Studies have shown that the catalytic active sites of two-dimensional transition metal sulfide materials are generally coordinated unsaturated atoms at the edge, while a large number of atoms on the basal surface do not actually participate in the catalytic process, thus failing to demonstrate the advantage of the high specific surface area of two-dimensional materials. Therefore, when preparing two-dimensional transition metal sulfide materials, more active edges need to be constructed on their two-dimensional layered structure. Currently, most sulfide preparations still use liquid phase co-precipitation to expand their specific surface area, but this method has limited effect on increasing the edge position of two-dimensional transition metal sulfide materials and cannot be separated from the two-dimensional layered structure. Therefore, the electrocatalytic hydrogen evolution performance of two-dimensional transition metal sulfide materials is still not ideal. Summary of the invention
[0005] In view of the deficiencies in the above-mentioned prior art, the present invention provides a ZIF-derived CoZnS electrode material and a preparation method and application thereof. The present invention uses a soluble cobalt salt and a soluble zinc salt as raw materials, uses NH4F as a buffer and a structure directing agent, and adopts urea to provide a weak alkaline environment. A foamed nickel-CoZn precursor is prepared by a solvent thermal reaction, and then the foamed nickel-CoZn precursor is coordinated with the foamed nickel-CoZn precursor through the coordination effect of dimethylimidazole. The foamed nickel-CoZn precursor has a small crystal form, so it will continuously transform into ZIF, promote the coordination reaction process, and then introduce a ZIF-67 structure to obtain a ZIF-derived precursor, and then control the sulfurization conditions of the ZIF-derived precursor to prepare a ZIF-derived CoZnS electrode material with a stable three-dimensional structure. The ZIF-derived CoZnS electrode material prepared by the method of the present invention has a large and uniform MOF structure and a three-dimensional array, which provides sufficient active sites and a stable physical structure for the subsequent electrocatalytic hydrogen evolution reaction. The CoZnS electrode material has more active edges and thus exhibits more catalytic sites, overcoming the technical defect of the low catalytic site density of the two-dimensional transition metal sulfide material in the prior art.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] The preparation method of the CoZnS electrode material derived from ZIF is characterized by comprising the following steps:
[0008] Soluble Zn salt and soluble Co salt are used as raw materials, NH4F is used as a buffer and a structure directing agent, the buffer can maintain the pH of the mixed solution, the structure directing agent can guide the growth of zinc cobalt hydroxide, urea is used to provide a weak alkaline environment, the soluble Zn salt, the soluble Co salt, NH4F and urea are mixed together in water to obtain a mixed solution, nickel foam is immersed in the mixed solution, and a solvothermal reaction is carried out to in situ grow zinc cobalt hydroxide with a lamellar array structure on a three-dimensional nickel foam substrate to obtain a nickel foam-CoZn precursor.
[0009] Dissolve dimethylimidazole in water to obtain a dimethylimidazole solution.
[0010] The nickel foam-CoZn precursor is immersed in a dimethylimidazole solution and allowed to stand. During the standing process, the dimethylimidazole coordinates with the zinc ions and cobalt ions on the nickel foam-CoZn precursor to form a large coordination group. The nickel foam-CoZn precursor has a small crystal form, so it will continue to transform into ZIF, promoting the coordination reaction process, and then introducing ZIF-67 into the nickel foam-CoZn precursor to obtain a ZIF-derived precursor.
[0011] The ZIF-derived precursor and Na2S were mixed in water and subjected to a hydrothermal reaction. During the hydrothermal process, S 2-An anion exchange reaction is carried out with the organic coordination groups on ZIF-67 to obtain a porous structure, and the zinc ions and cobalt ions of the ZIF-derived precursor are sulfided to obtain the ZIF-derived CoZnS electrode material.
[0012] Preferably, the Zn of the soluble Zn salt is 2+ Co with soluble Co salts 2+ The molar ratio of Zn is 1:1-3. 2+ With Co 2+ The molar ratio of Co 2+ The amount can be slightly higher than Zn 2+ The amount.
[0013] Preferably, in the mixed solution, the concentration of NH4F is 0.1-0.4 mol / L, and the concentration of urea is 0.2-0.4 mol / L, so that the pH of the mixed solution is greater than 7 and less than 9.
[0014] Preferably, the solvent thermal reaction conditions are: heating at 110-140° C. for 5-10 h.
[0015] Preferably, the mass ratio of dimethylimidazole to the CoZn precursor on the nickel foam-CoZn precursor is 50-70:1.
[0016] Preferably, the standing time is ≥ 2 h.
[0017] Preferably, the mass ratio of the ZIF-derived precursor minus the nickel foam to Na2S is 1:1-4, and the mass ratio of the two is obtained through experimental screening.
[0018] Preferably, the hydrothermal reaction conditions are: 6-10 hours at 80-100°C. If the hydrothermal time is too short, the sulfurization reaction is incomplete, the sulfide is not fully formed, and the porous structure is limited; if the hydrothermal time is too long, it will lead to excessive sulfurization, in which the sulfide will agglomerate and the specific surface area will decrease. If the temperature is too low, the reaction rate will be too low, and if the temperature is too high, the reaction will be too violent, destroying the overall structure of the CoZnS electrode material derived from ZIF.
[0019] The invention also protects the CoZnS electrode material derived from ZIF prepared by the preparation method.
[0020] The invention also protects the application of the CoZnS electrode material derived from ZIF in the preparation of the cathode material for electrocatalytic hydrogen evolution.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention uses soluble Zn salt, soluble Co salt, NH4F, urea and nickel foam as raw materials, and first prepares a nickel foam-CoZn precursor through a solvent thermal reaction, wherein NH4F is a buffer and a structure directing agent, and urea provides a weakly alkaline environment. In the obtained nickel foam-CoZn precursor, zinc cobalt hydroxide with a sheet array structure is prepared on a three-dimensional nickel foam substrate, and the sheets are interlaced with each other, so it has a large specific surface area, which provides a large-area template for the subsequent synthesis of CoZnS electrode materials derived from ZIF; then the nickel foam-CoZn precursor is immersed in dimethylamidite In the azole, dimethylimidazole coordinates with zinc ions and cobalt ions, and the nickel foam-CoZn precursor has a small crystal form, so it will continuously transform to ZIF, promote the coordination reaction process, and then introduce ZIF-67 in situ on the nickel foam-CoZn precursor, that is, ZIF-67 is directly transformed and grown on the nickel foam-CoZn precursor sheet, so it inherits the large specific surface area of the nickel foam-CoZn precursor. At the same time, the present invention combines the metal precursor with the organic ligand to form a metal organic ligand to obtain a ZIF-derived precursor; then the ZIF-derived precursor is sulfurized with sodium sulfide. During the sulfurization process, S 2- The organic coordination groups on ZIF-67 undergo anion exchange reaction, and the organic coordination groups with larger radius come out of ZIF-67, while the S 2- Entering into ZIF-67, further pore formation was carried out to further expand the specific surface area. The increased specific surface area resulted in more active edges and increased catalytic site density, thus obtaining ZIF-derived CoZnS electrode material.
[0023] 2. The ZIF-derived CoZnS electrode material prepared by the method of the present invention has a large specific surface area and sufficient catalytic sites, which is due to the array framework and MOF three-dimensional structure of the ZIF-derived CoZnS electrode material; the array framework is derived from: the CoZn precursor array framework is prepared by a solvothermal method, and then the ZIF is introduced in situ on the array framework, and finally S 2- The anion exchange reaction is carried out with the organic coordination groups in ZIF, and pores are further formed on the basis of maintaining the array framework. The obtained ZIF-derived CoZnS electrode material has the advantages of large specific surface area, controllable structure and adjustable porosity, overcoming the technical defects of the existing two-dimensional transition metal sulfide materials that the effect of increasing the edge position is limited, resulting in low catalytic site density.
[0024] 3. The present invention uses nickel foam as a substrate, and zinc cobalt hydroxide is loaded on the substrate to obtain a nickel foam-CoZn precursor, and then the ZIF structure is introduced in situ on this basis, and finally the ZIF-derived CoZnS electrode material is obtained by sulfurization. Among them, nickel foam provides a stable growth skeleton for ZIF, and its excellent conductivity accelerates the electron transfer rate of the CoZnS electrode material; sacrificial template zinc cobalt hydroxide is used to achieve orderly arrangement of MOF, and a three-dimensional ZIF-derived CoZnS electrode material is constructed. At this time, ZIF provides more active edges for the CoZnS electrode material, showing more catalytic sites; the CoZnS electrode material has a binary metal center, and the synergistic catalytic effect between CoS and ZnS promotes the adsorption and desorption reaction steps of active hydrogen atoms in the hydrogen evolution reaction, thereby improving the efficiency of hydrogen production.
[0025] 4. The results of analyzing the prepared ZIF-derived CoZnS electrode material show that the ZIF-derived CoZnS electrode material has excellent catalytic activity. The ZIF-derived CoZnS electrode material has a stable structure and is in the form of nanosheets and nanowires, which means that the ZIF-derived CoZnS electrode material has a large specific surface area, can provide more active sites, and has a small impedance radius. The ZIF-derived CoZnS electrode material is easier to react and the electron transfer is faster.
[0026] 5. The present invention provides a method for achieving orderly arrangement of MOF using a sacrificial template zinc cobalt hydroxide and constructs a three-dimensional catalyst. The method of the present invention has good feasibility and provides a demonstration for the construction of subsequent three-dimensional catalytic materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The SEM images of the CoZnS-0.2 electrode of Example 2 at different magnifications, wherein (a) is a low magnification image and (b) is a high magnification image.
[0028] Figure 2 In the figure, (a) is the XRD diagram of the NF-CoZn precursor of Example 1, (b) is the XRD diagram of the ZIF of Example 1, and (c) is the XRD diagram of the CoZnS of Example 2.
[0029] Figure 3In the figure, (a) is the LSV diagram of the CoZnS-0.1 electrode of Example 1, the CoZnS-0.2 electrode of Example 2, the CoZnS-0.3 electrode of Example 3, and the CoZnS-0.4 electrode of Example 4, and (b) is the EIS diagram of the CoZnS-0.1 electrode of Example 1, the CoZnS-0.2 electrode of Example 2, the CoZnS-0.3 electrode of Example 3, and the CoZnS-0.4 electrode of Example 4.
[0030] Figure 4 In the figure, (a) is the LSV graph of the NF-Zn precursor of Comparative Example 1, the NF-Co precursor of Comparative Example 2, and the NF-CoZn precursor of Example 1, and (b) is the EIS graph of the NF-Zn precursor of Comparative Example 1, the NF-Co precursor of Comparative Example 2, and the NF-CoZn precursor of Example 1. DETAILED DESCRIPTION
[0031] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.
[0032] Under standard conditions, the free energy of water decomposition becomes 237.2 kJ mol -1 According to the Nernst equation, the theoretical decomposition voltage of water is 1.23V. In fact, electrochemical processes usually face electrochemical polarization, concentration polarization and solution resistance factors. These factors work together to make the electrode potential unable to maintain a theoretical equilibrium state, thereby generating additional overpotential. In order to address this challenge and improve system performance, the use of efficient electrocatalysts becomes crucial. The ZIF-derived CoZnS electrode material provided by the present invention can effectively reduce the additional energy required in the water decomposition process, i.e., the overpotential, thereby enhancing the efficiency of energy conversion.
[0033] The technical solution of the present invention is studied using embodiments and comparative examples below, and the specific research methods and results are as follows:
[0034] Example 1
[0035] The preparation method of the ZIF-derived CoZnS electrode material comprises the following steps:
[0036] S1. Cleaning the nickel foam by using deionized water and ethanol to alternately ultrasonically clean the nickel foam for 10 seconds each time to obtain clean nickel foam.
[0037] S2, weigh 0.22g Zn(NO3)2, 0.44g Co(NO3)2, 0.22g NH4F and 0.9g urea, and then dissolve them together in 60mL deionized water. 2+ With Co 2+ The molar ratio of NH4F is 1:2, the concentration of NH4F is 0.2mol / L, the concentration of urea is 0.25mol / L, and the mixture is stirred at room temperature for 10 min. The mixture is transferred into a 100mL reactor, and the clean foamed nickel obtained in step S1 is placed in the reactor. The mixture is then placed in a forced air drying oven and reacted at 120°C for 6 h. The product is collected, washed, and vacuum dried at 60°C to obtain a foamed nickel-CoZn precursor, which is referred to as NF-CoZn precursor.
[0038] S3. Dissolve 1.25 g of dimethylimidazole in 20 mL of deionized water and stir evenly to obtain a dimethylimidazole solution. Place the NF-CoZn precursor of step S2 in the dimethylimidazole solution and let it stand for 3 hours. At this time, the mass ratio of dimethylimidazole to the CoZn precursor on the nickel foam-CoZn precursor is 50:1. Then wash and dry for 6 hours to obtain a ZIF-derived precursor.
[0039] S4. Take 0.1 g of Na2S and dissolve it in 60 mL of deionized water to obtain a Na2S solution. Place the ZIF-derived precursor in the Na2S solution. At this time, the mass ratio of the ZIF-derived precursor minus the nickel foam to Na2S is 1:1. Perform a hydrothermal reaction at 90°C in a reactor for 8 hours, and then vacuum dry at 60°C to constant weight to obtain a CoZnS-0.1 electrode.
[0040] Example 2
[0041] The preparation method of the ZIF-derived CoZnS electrode material is the same as the preparation steps of Example 1, except that the mass of Na2S is replaced from 0.1 g to 0.2 g, and includes the following steps:
[0042] S1. Cleaning the nickel foam to obtain clean nickel foam.
[0043] S2. Weigh 0.22 g of Zn(NO3)2, 0.44 g of Co(NO3)2, 0.22 g of NH4F and 0.9 g of urea, and then dissolve them together in 60 mL of deionized water. After stirring at room temperature for 10 min, move them into a 100 mL reactor. Put the clean foam nickel of step S1 into the reactor, and then place it in a forced air drying oven. After reacting at 120°C for 6 h, collect the product, wash it in turn, and vacuum dry it at 60°C to obtain a foam nickel-CoZn precursor, recorded as NF-CoZn precursor.
[0044] S3. Dissolve 1.25 g of dimethylimidazole in 20 mL of deionized water and stir evenly to obtain a dimethylimidazole solution. Place the NF-CoZn precursor of step S2 in the dimethylimidazole solution and let stand for 3 hours, then wash and dry for 6 hours to obtain a ZIF-derived precursor.
[0045] S4. Take 0.2 g of Na2S and dissolve it in 60 mL of deionized water to obtain a Na2S solution. Place the ZIF-derived precursor in the Na2S solution. At this time, the mass ratio of the ZIF-derived precursor minus the nickel foam to Na2S is 1:2. Perform a hydrothermal reaction at 90°C in a reactor for 8 hours, and then vacuum dry at 60°C to constant weight to obtain a CoZnS-0.2 electrode.
[0046] Example 3
[0047] The preparation method of the ZIF-derived CoZnS electrode material is the same as the preparation steps of Example 1, except that the mass of Na2S is replaced from 0.1 g to 0.3 g, and comprises the following steps:
[0048] S1. Cleaning the nickel foam to obtain clean nickel foam.
[0049] S2. Weigh 0.22 g of Zn(NO3)2, 0.44 g of Co(NO3)2, 0.22 g of NH4F and 0.9 g of urea, and then dissolve them together in 60 mL of deionized water. After stirring at room temperature for 10 min, move them into a 100 mL reactor. Put the clean foam nickel of step S1 into the reactor, and then place it in a forced air drying oven. After reacting at 120°C for 6 h, collect the product, wash it in turn, and vacuum dry it at 60°C to obtain a foam nickel-CoZn precursor, recorded as NF-CoZn precursor.
[0050] S3. Dissolve 1.25 g of dimethylimidazole in 20 mL of deionized water and stir evenly to obtain a dimethylimidazole solution. Place the NF-CoZn precursor of step S2 in the dimethylimidazole solution and let stand for 3 hours, then wash and dry for 6 hours to obtain a ZIF-derived precursor.
[0051] S4. Take 0.3 g of Na2S and dissolve it in 60 mL of deionized water to obtain a Na2S solution. Place the ZIF-derived precursor in the Na2S solution. At this time, the mass ratio of the ZIF-derived precursor minus the nickel foam to Na2S is 1:3. Perform a hydrothermal reaction at 90°C in a reactor for 8 hours, and then vacuum dry at 60°C to constant weight to obtain a CoZnS-0.3 electrode.
[0052] Example 4
[0053] The preparation method of the ZIF-derived CoZnS electrode material is the same as the preparation steps of Example 1, except that the mass of Na2S is replaced from 0.1 g to 0.4, and comprises the following steps:
[0054] S1. Cleaning the nickel foam to obtain clean nickel foam.
[0055] S2. Weigh 0.22 g of Zn(NO3)2, 0.44 g of Co(NO3)2, 0.22 g of NH4F and 0.9 g of urea, and then dissolve them together in 60 mL of deionized water. After stirring at room temperature for 10 min, move them into a 100 mL reactor. Put the clean foam nickel of step S1 into the reactor, and then place it in a forced air drying oven. After reacting at 120°C for 6 h, collect the product, wash it in turn, and vacuum dry it at 60°C to obtain a foam nickel-CoZn precursor, recorded as NF-CoZn precursor.
[0056] S3. Dissolve 1.25 g of dimethylimidazole in 20 mL of deionized water and stir evenly to obtain a dimethylimidazole solution. Place the NF-CoZn precursor of step S2 in the dimethylimidazole solution and let stand for 3 hours, then wash and dry for 6 hours to obtain a ZIF-derived precursor.
[0057] S4. Take 0.4 g of Na2S and dissolve it in 60 mL of deionized water to obtain a Na2S solution. Place the ZIF-derived precursor in the Na2S solution. At this time, the mass ratio of the ZIF-derived precursor minus the nickel foam to Na2S is 1:4. Perform a hydrothermal reaction at 90°C in a reactor for 8 hours, and then vacuum dry at 60°C to constant weight to obtain a CoZnS-0.4 electrode.
[0058] Example 5
[0059] The preparation method of the ZIF-derived CoZnS electrode material comprises the following steps:
[0060] S1. Cleaning the nickel foam by using deionized water and ethanol to alternately ultrasonically clean the nickel foam for 10 seconds each time to obtain clean nickel foam.
[0061] S2, weigh 0.22g Zn(NO3)2, 0.22g Co(NO3)2, 0.11g NH4F and 1.44g urea, and then dissolve them together in 60mL deionized water. 2+ With Co 2+The molar ratio of NH4F is 1:1, the concentration of NH4F is 0.1 mol / L, the concentration of urea is 0.4 mol / L, and after continuous stirring at room temperature for 10 min, the mixture is transferred into a 100 mL reactor, and the clean foamed nickel of step S1 is placed in the reactor, and then placed in a forced air drying oven. After reacting at 140 ° C for 5 h, the product is collected, washed, and vacuum dried at 60 ° C to obtain a foamed nickel-CoZn precursor, which is recorded as NF-CoZn precursor.
[0062] S3. Dissolve dimethylimidazole in 20 mL of deionized water and stir evenly to obtain a dimethylimidazole solution. Place the NF-CoZn precursor of step S2 in the dimethylimidazole solution and let it stand for 3 hours. At this time, the mass ratio of dimethylimidazole to the CoZn precursor on the nickel foam-CoZn precursor is 60:1. Then wash and dry for 6 hours to obtain a ZIF-derived precursor.
[0063] S4. Take 0.2 g of Na2S and dissolve it in 60 mL of deionized water to obtain a Na2S solution. Place the ZIF-derived precursor in the Na2S solution, perform a hydrothermal reaction at 80° C. in a reactor for 10 h, and then vacuum dry at 60° C. to constant weight to obtain a ZIF-derived CoZnS electrode material.
[0064] Example 6
[0065] The preparation method of the ZIF-derived CoZnS electrode material comprises the following steps:
[0066] S1. Cleaning the nickel foam by using deionized water and ethanol to alternately ultrasonically clean the nickel foam for 10 seconds each time to obtain clean nickel foam.
[0067] S2, weigh 0.22g Zn(NO3)2, 0.66g Co(NO3)2, 0.44g NH4F and 0.72g urea, and then dissolve them together in 60mL deionized water. 2+ With Co 2+ The molar ratio of NH4F is 1:3, the concentration of NH4F is 0.4 mol / L, the concentration of urea is 0.2 mol / L, and after continuous stirring at room temperature for 10 min, the mixture is transferred into a 100 mL reactor, and the clean foamed nickel of step S1 is placed in the reactor, and then placed in a forced air drying oven. After reacting at 110 ° C for 10 h, the product is collected, washed, and vacuum dried at 60 ° C to obtain a foamed nickel-CoZn precursor, which is recorded as NF-CoZn precursor.
[0068] S3. Dissolve dimethylimidazole in 20 mL of deionized water and stir evenly to obtain a dimethylimidazole solution. Place the NF-CoZn precursor of step S2 in the dimethylimidazole solution and let it stand for 3 hours. At this time, the mass ratio of dimethylimidazole to the CoZn precursor on the nickel foam-CoZn precursor is 70:1. Then wash and dry for 6 hours to obtain a ZIF-derived precursor.
[0069] S4. Take 0.3 g of Na2S and dissolve it in 60 mL of deionized water to obtain a Na2S solution. Place the ZIF-derived precursor in the Na2S solution, perform a hydrothermal reaction at 100° C. in a reactor for 6 h, and then vacuum dry at 60° C. to constant weight to obtain a ZIF-derived CoZnS electrode material.
[0070] Comparative Example 1
[0071] The preparation method of the NF-Zn precursor is the same as that of Example 1, except that the reactant does not contain Co(NO3)2, and comprises the following steps:
[0072] Take 0.22g of Zn(NO3)2, 0.22g of NH4F and 0.9g of urea and dissolve them in 60mL of deionized water. After stirring at room temperature for 10min, transfer them into a 100mL reactor. Put the cleaned nickel foam into the reactor and put it into a forced air drying oven. After reacting at 120℃ for 6h, collect and wash the product, and then vacuum dry it at 60℃ to obtain NF-Zn precursor.
[0073] Comparative Example 2
[0074] The preparation method of the NF-Co precursor is the same as that of Example 1, except that the reactant does not contain Zn(NO3)2, and comprises the following steps:
[0075] Take 0.44g of Co(NO3)2, 0.22g of NH4F and 0.9g of urea and dissolve them in 60mL of deionized water. After stirring at room temperature for 10min, transfer them into a 100mL reactor. Put the cleaned nickel foam into the reactor and put it into a forced air drying oven. After reacting at 120℃ for 6h, collect and wash the product, and then vacuum dry it at 60℃ to obtain the NF-Co precursor.
[0076] The ZIF-derived CoZnS electrode materials of Examples 1-6 of the present invention all have excellent electrocatalytic hydrogen evolution performance and can achieve a larger hydrogen evolution reaction current under lower overpotential conditions, i.e., higher hydrogen evolution efficiency. The ZIF-derived CoZnS electrode materials of Examples 1-4 are used as examples for research, and compared with the NF-Zn precursor of Comparative Example 1 and the NF-Co precursor of Comparative Example 2. The specific research methods and results are as follows:
[0077] Figure 1 (a) is a SEM image of the CoZnS-0.2 electrode of Example 2 at a low magnification. As can be seen from the figure, the surface distribution of the prepared CoZnS-0.2 electrode is uniform and the structure is stable, which enables the CoZnS-0.2 electrode to maintain a high activity after multiple uses, thereby extending the service life of the ZIF-derived CoZnS electrode material. Figure 1 (b) is a SEM image of the CoZnS-0.2 electrode at high magnification. It can be seen from the figure that the prepared CoZnS-0.2 electrode presents uniform, thin nanosheets and nanowires, with a sheet thickness of about 100μm. The SEM image shows both nanowire and nanosheet structures. The nanowire structure provides a high specific surface area and excellent electron transfer path, which is conducive to rapid charge transfer and high reactivity. The nanosheet structure usually has a large plane size and a relatively small thickness. Such a structure can further increase the specific surface area of the CoZnS electrode, especially in the direction perpendicular to the plane of the ZIF-derived CoZnS electrode material, which is conducive to the rapid diffusion and adsorption or desorption process of electrolyte ions, which is very beneficial to improving electrochemical energy storage and conversion efficiency.
[0078] Figure 2 (a) is the XRD pattern of NF-CoZn precursor. By comparing the peaks with diffraction angles of 18°, 32°, and 58°, which correspond to the (001), (101), and (110) crystal planes of the cobalt hydroxide PDF standard card, it is shown that the NF-CoZn precursor exists in the form of cobalt hydroxide. There are some peak shifts in the image, which is caused by the doping of zinc in the NF-CoZn precursor. Figure 2 (b) is the XRD pattern of ZIF. By comparing with the standard card, it was concluded that the prepared sample was ZIF-67. Figure 2 (c) is the XRD pattern of the CoZnS-0.2 electrode of Example 2. The peaks at diffraction angles of 31°, 38°, and 55° correspond to the (311), (400), and (440) crystal planes of the cobalt sulfide PDF standard card (PDF#42-1448), respectively, indicating that sulfur is indeed incorporated into the final sample. Through XRD image analysis, the present invention successfully prepared NF-CoZn precursors, ZIF-derived precursors, and ZIF-derived CoZnS electrode materials.
[0079] In order to further explore the electrocatalytic activity of the prepared ZIF-derived CoZnS electrode material, LSV and EIS tests were carried out on the electrode material. The catalytic hydrogen evolution activity of the prepared ZIF-derived CoZnS electrode material was tested in 1 mol / L NaOH solution using a typical three-electrode system.
[0080] Construction of a three-electrode system: The ZIF-derived CoZnS electrode materials of Examples 1-4 were used as working electrodes, the Hg / HgO electrode was used as the reference electrode, and the platinum electrode was used as the counter electrode. One end of the working electrode, the reference electrode, and the counter electrode were placed in a 1 mol / L NaOH solution, and the other ends were electrically connected to the electrochemical workstation.
[0081] Figure 3 (a) LSV diagrams of CoZnS-0.1 electrode, CoZnS-0.2 electrode, CoZnS-0.3 electrode and CoZnS-0.4 electrode. -2 ), the CoZnS-0.2 electrode has a smaller overpotential of 350mV, and the overpotentials of CoZnS-0.1, CoZnS-0.3, and CoZnS-0.4 electrodes are 400mV, 450mV, and 460mV, respectively. The CoZnS-0.2 electrode has a smaller overpotential, which shows that the CoZnS-0.2 electrode has the best hydrogen evolution performance.
[0082] Figure 3 (b) is the EIS graph of CoZnS-0.1 electrode, CoZnS-0.2 electrode, CoZnS-0.3 electrode and CoZnS-0.4 electrode. As can be seen from the figure, the CoZnS-0.2 electrode has a smaller impedance radius, with an impedance of 20Ω. The impedance radii of the CoZnS-0.1 electrode, CoZnS-0.3 electrode and CoZnS-0.4 electrode increase successively, with impedances of 30Ω, 33Ω and 43Ω respectively. The CoZnS-0.2 electrode has the smallest impedance radius, indicating that the electron transfer resistance is low, which means that the CoZnS-0.2 electrode reaction is easier to proceed and the electron transfer is faster. It means that the catalytic activity is high, and the smaller impedance represents that the catalytic layer has less resistance to the reaction, which makes the reaction rate faster and the possibility of electron recombination is reduced. This can also correspond to the above SEM figure. The ZIF-derived CoZnS electrode material obtained after sulfurization has a larger specific surface area and better catalytic performance.
[0083] As a comparative experiment, the amounts of Co and Zn were changed to prepare NF-Co precursor and NF-Zn precursor, respectively. Figure 4 (a) is the LSV diagram of the NF-Co precursor of Comparative Example 2, the NF-Zn precursor of Comparative Example 1, and the NF-CoZn precursor of Example 1. It can be seen from the figure that at the same current density (100 mA cm -2), the overpotential of NF-CoZn precursor is the lowest, which is 320mV. The overpotentials of NF-Zn precursor and NF-Co precursor are 350mV and 380mV respectively. It can be judged that the catalytic performance of NF-CoZn precursor is better. At the same time, it is calculated that the Tafel slope of NF-CoZn precursor is small, which means that in the electrochemical reaction, as the current density increases, the required overpotential increases relatively slowly. The reaction kinetics are more favorable, and the electron transfer on the surface of ZIF-derived CoZnS electrode material is relatively rapid, so that a higher reaction rate can be achieved at a lower overpotential.
[0084] Figure 4 (b) is the EIS graph of the NF-Co precursor of Comparative Example 2, the NF-Zn precursor of Comparative Example 1, and the NF-CoZn precursor of Example 1. It can be seen from the figure that the impedance radius of the NF-CoZn precursor is relatively small, with a size of 40Ω, and the impedance radius of the NF-Zn precursor and the NF-Co precursor increases successively, with impedances of 70Ω and 130Ω respectively. The NF-CoZn precursor has the smallest impedance radius, the best catalytic performance, and a faster electron transfer speed. When compared with the NF-Zn precursor and the NF-Co precursor, it is judged that the NF-CoZn precursor has a larger specific surface area, more active sites, and can fully contact with the reactants, thereby accelerating the chemical reaction, thereby accelerating the reaction rate and improving the catalytic efficiency.
[0085] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalent technologies, the present invention is also intended to include these changes and variations. The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and their protection scope is not limited thereto. Equivalent substitutions or changes made by those skilled in the art on the basis of the present invention are all within the protection scope of the present invention, and the protection scope of the present invention shall be subject to the claims.
Claims
1. A method for preparing a ZIF-derived CoZnS electrode material, characterized in that: The steps include: Using soluble Zn salt and soluble Co salt as raw materials, NH4F as a buffer and structure directing agent, and urea to provide a weak alkaline environment, the soluble Zn salt, the soluble Co salt, NH4F and urea are mixed in water to obtain a mixed solution, and nickel foam is immersed in the mixed solution, and a solvothermal reaction is performed to in-situ grow zinc cobalt hydroxide on the nickel foam to obtain a nickel foam-CoZn precursor; Dissolving dimethylimidazole in water to obtain a dimethylimidazole solution; The nickel foam-CoZn precursor is immersed in a dimethylimidazole solution and allowed to stand. During the standing process, the dimethylimidazole coordinates with the zinc ions and cobalt ions on the nickel foam-CoZn precursor to obtain a ZIF-derived precursor; The ZIF-derived precursor and Na2S were mixed in water and subjected to a hydrothermal reaction. During the hydrothermal process, S 2- An anion exchange reaction is carried out with the organic coordination groups on ZIF-67 to obtain a porous structure, and the zinc ions and cobalt ions of the ZIF-derived precursor are sulfided to obtain the ZIF-derived CoZnS electrode material.
2. The method for preparing the ZIF-derived CoZnS electrode material according to claim 1, characterized in that: Zn in soluble Zn salts 2+ Co with soluble Co salts 2+ The molar ratio is 1:1-3.
3. The method for preparing the ZIF-derived CoZnS electrode material according to claim 1, characterized in that: In the mixed solution, the concentration of NH4F is 0.1-0.4 mol / L, and the concentration of urea is 0.2-0.4 mol / L.
4. The method for preparing the ZIF-derived CoZnS electrode material according to claim 1, characterized in that: The conditions of the solvothermal reaction are: heating at 110-140°C for 5-10h.
5. The method for preparing the ZIF-derived CoZnS electrode material according to claim 1, characterized in that: The mass ratio of dimethylimidazole to the CoZn precursor on the nickel foam-CoZn precursor is 50-70:
1.
6. The method for preparing the ZIF-derived CoZnS electrode material according to claim 1, characterized in that: Standing time ≥ 2h.
7. The method for preparing the ZIF-derived CoZnS electrode material according to claim 1, characterized in that: The mass ratio of the ZIF-derived precursor minus the nickel foam to Na2S is 1:1-4.
8. The method for preparing the ZIF-derived CoZnS electrode material according to claim 1, characterized in that: The conditions of the hydrothermal reaction are: hydrothermal reaction at 80-100°C for 6-10h.
9. A ZIF-derived CoZnS electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the ZIF-derived CoZnS electrode material according to claim 9 in preparing an electrocatalytic hydrogen evolution cathode material.
Citation Information
Patent Citations
Multi-metal MOFs derived oxygen reduction / oxygen evolution double-function catalytic material, and preparation method thereof
CN109926084A
Method for vulcanization modification of ZIF-67 and application
CN113134394A
Electrocatalytic oxygen evolution catalyst and preparation method thereof
CN113403638A
Zeolite imidazate skeleton derived electrocatalyst, and preparation method and application thereof
CN115874217A
Multi-metal sulfide electrocatalyst, preparation method and application
CN118988366A
Cited By
Transition metal phosphide electrode material and preparation method thereof
CN120158765A